The uses of tropical grasses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Tropical grasses by P J Skerman and Fernando Riveros 832 pp, 1989 ISBN 92-5-1001 128 1 FAO Plant Production and Protection Series no. 2 Distribution and Sales Section Via delle Terme di Caracalla 00100 Rome ITALY